Developing an Islamic History Board Game to Enhance Learning Interest among Grade 6 Primary Students: An ADDIE-Based Study - Moch Ilham Firmansyah; Dian Mohammad Hakim; Moh. Muslim Moh. Muslim; Mohammad Afifullah (Papanda Publisher, 2026)
This study developed and evaluated The Andalus educational board game to enhance Grade 6 students' interest in learning Islamic History, specifically the Umayyad dynasty in Andalusia. Using the ADDIE instructional design model, the study systematically conducted analysis, design, development, implementation, and evaluation phases. The analysis phase identified students' low affective engagement and motivation toward Islamic History learning through teacher interviews and classroom observations. The design phase integrated historically accurate content with age-appropriate game mechanics, while the development phase refined the prototype through expert validation focusing on content accuracy (94.6%) and media quality (97.6%). Implementation involved small-scale (n=10) and large-scale (n=30) classroom trials to examine instructional feasibility and effectiveness. Student response questionnaires yielded high effectiveness scores of 91.0% and 92.06% respectively, while teacher evaluation reached 86.15%. Classroom observations revealed unexpected cognitive outcomes, including spontaneous counterfactual reasoning and peer-mediated learning. The findings demonstrate that The Andalus board game represents a valid and effective instructional medium that enhances students' learning interest through collaborative gameplay, cultural engagement, and interactive historical exploration. The study contributes to game-based learning theory by demonstrating the pedagogical viability of analogue board games in Islamic History education, offering teachers a culturally relevant, low-cost instructional tool for primary education contexts.